2004
DOI: 10.1242/jeb.01058
|View full text |Cite
|
Sign up to set email alerts
|

Basolateral ion transport mechanisms during fluid secretion byDrosophilaMalpighian tubules: Na+ recycling,Na+:K+:2Cl– cotransport and Cl– conductance

Abstract: SUMMARY Mechanisms of ion transport during primary urine formation by the Malpighian tubule of Drosophila melanogaster were analyzed through measurements of fluid secretion rate, transepithelial ion flux, basolateral membrane potential (Vbl) and intracellular activities of K+ (aKi) and Cl–(aCli). Calculation of the electrochemical potentials for both ions permitted assessment of the possible contributions of K+ channels, Na+:K+:2Cl–cotransport, and K+:Cl– cotransport, to net transepithelial ion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 50 publications
4
44
0
Order By: Relevance
“…Therefore the simulations suggest that the depolarizing role of GABA dominates its effects on VS-3 neurons stimulated by randomly varying membrane current. This finding is consistent with a previous report where a simulated model of spinal cord neurons revealed that shunting was a local effect while the depolarization was longer lasting, spreading electrotonically in the somatodendritic tree leading to excitation (Jean-Xavier et al 2007). …”
Section: Depolarization Shunting and Gaba-induced Excitationsupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore the simulations suggest that the depolarizing role of GABA dominates its effects on VS-3 neurons stimulated by randomly varying membrane current. This finding is consistent with a previous report where a simulated model of spinal cord neurons revealed that shunting was a local effect while the depolarization was longer lasting, spreading electrotonically in the somatodendritic tree leading to excitation (Jean-Xavier et al 2007). …”
Section: Depolarization Shunting and Gaba-induced Excitationsupporting
confidence: 93%
“…To learn whether the excitatory GABA response in VS-3 neurons could also be regulated by Cl Ϫ transporters we used the "loop" diuretics furosemide and bumetanide. In addition to NKCC1 these diuretics also inhibit KCC1, a K ϩ -Cl Ϫ cotransporter that actively extrudes Cl Ϫ from cells in vertebrate and invertebrate preparations (Cheung et al 2006;Deisz and Lux 1982;Gillen et al 2006;Hille and Walz 2006;Ianowski and O'Donnell 2004;Theander et al 1999). Furosemide has about equal potency for NKCC1 and KCC1, but bumetanide has a significantly higher affinity for NKCC1 (Payne et al 2003) and would therefore be more likely to affect the response of VS-3 neurons.…”
Section: Blocking Cation-chloride Cotransporter Function Reduced Gabamentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a decrease in intracellular chloride occurring during cell swelling and regulatory volume decrease could stimulate WNK through relief of chloride inhibition, followed by Fray and Ncc69 activation, stimulating an increase in transepithelial ion and water flux. Indeed, intracellular Cl Ϫ concentration in the fly tubule is 30 mM in isotonic conditions (72), slightly higher than the apparent median inhibitory concentration of 20 mM for Cl Ϫ inhibition of mammalian WNK1 autophosphorylation (71). This suggests that tubule WNK-Fray signaling is poised to respond to changes in intracellular Cl Ϫ .…”
Section: Discussionmentioning
confidence: 92%
“…Bumetanide is well-known as an inhibitor of basolateral Na + :K + :2Cl -cotransport in the Malpighian tubules of dipterans (Scott et al, 2004;Ianowski & O'Donnell, 2004) and other species (e.g. crickets; Coast, 2012).…”
Section: Discussionmentioning
confidence: 99%